Effects of musical training and culture on meter perception. (March 2017) - Yates, Charles M.; Justus, Timothy; Atalay, Nart Bedin; Mert, Nazike; Trehub, Sandra E.
Western music is characterized primarily by simple meters, but a number of other musical cultures, including Turkish, have both simple and complex meters. In Experiment 1, Turkish and American adults with and without musical training were asked to detect metrical changes in Turkish music with simple and complex meter. Musicians performed significantly better than nonmusicians, and performance was significantly better on simple meter than on complex meter, but Turkish listeners performed no differently than American listeners. In Experiment 2, members of Turkish classical and folk music clubs who were tested on the same materials exhibited comparable sensitivity to simple and complex meters, unlike the American and Turkish listeners in Experiment 1. Together, the findings reveal important effects of musical training and culture on meter perception: trained musicians are generally more sensitive than nonmusicians, regardless of metrical complexity, but sensitivity to complex meter requires sufficient exposure to musical genres featuring such meters.